Study About High Influence Doping to Base Resistance and Bandgap Narrowing at Si/Si1-xGex/Si Heterojunction Bipolar Transistor - Fadhol, Achmad (Makara Journal of Technology, 2003)
Study About High Influence Doping to Base Resistance and Bandgap Narrowing at Si/Si1-xGex/Si Heterojunction Bipolar Transistor. Heterojunction is a link formed bedween two semiconductor materials and differend bandgap which has thinness under 50nm and grow the mixture of plate SiGe as bases. The link is an abrupt link or graded one. In this research learnt formulation of doping concentration influence to basis resistance and bandgap narrowing through Si/Si1-xGex/Si Heterojunction Bipolar Transistor with abrupt emitter-basis link, besides taking care to mobility and basis wide to basis resistance, it is also influence of mole fraction to bandgap power. From the result shows that doping concentration addition of NB=5.1018 cm-3 to NB=5.1020 cm-3 in basis can decrease resistance basis value about 3.6%, increase bandgap narrowing about 0.126, and increase collector current density for about 1.36 times to Ge 24%.